Solid electrolyte based on bead type MOF-808 network and preparation method thereof
By combining the beaded MOF-808 network with the polyacrylonitrile fiber network in the polymer electrolyte, the problem of uneven dispersion of MOF particles is solved, the effective utilization of MOF materials is achieved, and the transmission efficiency of lithium ions and the stability of electrochemical properties is improved.
Patent Information
- Application Number
- CN202411626783.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the metal organic frame (MOF) materials are unevenly dispersed in polymer electrolytes, and cannot effectively exert the advantages of porous, high specific surface area and active sites of MOF materials, resulting in unstable electrochemical performance.
The beaded MOF-808 network is used to combine with the polyacrylonitrile (PAN) fiber network to grow MOF-808 crystals in situ through hydrothermal reaction under high temperature and high pressure conditions, and beaded MOF-808 particles are loaded on the fiber surface to form a continuous MOF chain to ensure the compatibility of MOF materials and polymer matrix.
The uniform dispersion and effective utilization of MOF materials in polymer electrolytes is achieved, the transmission efficiency of lithium ions and the stability of electrochemical performance is improved, and the long-term cycle stability of solid-state lithium batteries is optimized.
Smart Images

Figure CN119542520A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid polymer electrolyte materials, and in particular relates to a solid electrolyte based on a beaded MOF-808 network and a preparation method thereof. Background Art
[0002] In order to solve the safety hazards of traditional organic liquid electrolytes, such as leakage, fire and explosion, solid-state lithium metal batteries have become the first choice for next-generation energy storage devices due to their excellent energy density and improved safety performance. Among the many solid electrolytes, solid polymer electrolytes have attracted much attention due to their flexibility, cost-effectiveness and adjustability, especially polyethylene oxide-based electrolytes, which have strong Li + The solvation ability and high dielectric constant make it particularly outstanding. However, single solid polymer electrolytes still have defects such as low ionic conductivity, unsatisfactory Li+ transfer number and inherent softness, which limit their widespread application in the field of lithium-ion batteries. Composite solid electrolytes have become a hot topic of research by integrating the advantages of polymer electrolytes and inorganic electrolytes. However, the existence of particle agglomeration of inorganic fillers leads to discontinuous lithium ion transmission, resulting in unstable electrochemical performance. Therefore, the key to the preparation of composite solid electrolytes is to balance the compatibility between polymers and additives to achieve optimal electrochemical performance.
[0003] Metal organic frameworks (MOFs) have the advantages of high specific surface area, rich porosity, and adjustable pore size. They can provide sufficient Lewis acid sites to limit the movement of anionic groups. In addition, the unique framework structure of MOF can provide Li+ transport paths, thereby effectively improving the ionic conductivity of polymer electrolytes. Therefore, it has many advantages over traditional inorganic nanoparticles and is a potential filler for solid electrolytes. Previous research has proposed the preparation of MOF particles and the preparation of polymer electrolytes by mixing polymer matrices in a physical and mechanical manner. For example, patent CN117558973A discloses a method of incorporating a prepared H-UIO-66 powder into a polyethylene oxide polymer matrix to obtain a MOFs-based solid polymer electrolyte; patent CN115842159A discloses a method of directly dispersing MOF5-NH-2 powder into polyethylene oxide and polyvinylidene fluoride polymer matrices to obtain a polymer-based composite solid electrolyte. However, due to the physical agglomeration effect, MOF particle powder cannot be evenly and effectively dispersed in the polymer electrolyte, resulting in uneven electrolyte lithium deposition and unstable performance. Later research work was improved by adding MOF particles to the electrospinning solution, so that the MOF particles formed a three-dimensional interconnected network system. For example, patent CN118198481A proposed to load MOF materials into three-dimensional fiber networks PAN and PVDF-HFP respectively, and the resulting solid electrolyte composite membrane has a three-dimensional porous structure. However, the MOF material is wrapped inside the fiber, and the Lewis acid sites cannot be effectively exposed to play its advantages of porosity, high specific surface area and adsorption of larger ions.
[0004] Therefore, there is an urgent need to design a method that can optimally integrate metal-organic framework (MOF) materials into polymer electrolytes to ensure their compatibility with polymers while maximizing the unique advantages of the MOF materials themselves to enhance the electrochemical performance of composite solid electrolytes. Summary of the invention
[0005] The present invention provides a solid electrolyte based on a beaded MOF-808 network and a preparation method thereof, so as to solve the problems in the prior art that the particles of the metal organic framework are unevenly dispersed when applied to the polymer electrolyte, and the unique advantages of the MOF crystal porosity, abundant active sites and high specific surface area for screening lithium salt anions and cations and capturing anions to promote lithium ion transmission cannot be effectively utilized.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A solid electrolyte based on a beaded MOF-808 network, wherein the beaded MOF-808 fiber network is a polyacrylonitrile (PAN) fiber as a carrier, and under high temperature and high pressure reaction conditions and hot pressing procedures, a single crystal structure of large-particle MOF-808 with a regular octahedral structure is loaded on the fiber network in a beaded manner; the beaded MOF-808 network structure is wrapped in a polymer matrix to form an efficient accelerator that promotes ion transmission. The specific preparation method comprises the following steps:
[0008] (1) preparing a polyacrylonitrile spinning solution with a certain mass fraction, and obtaining a polyacrylonitrile fiber membrane by electrospinning;
[0009] (2) preparing a MOF-808 precursor solution and fully dissolving and mixing it by ultrasonic oscillation;
[0010] (3) pouring the MOF-808 precursor solution described in step (2) into the inner tank of the reaction kettle, and cutting the fiber membrane obtained in step (1) into an appropriate size and immersing it in the precursor solution;
[0011] (4) placing the reactor liner of step (3) in a reactor, and performing a hydrothermal reaction under high temperature and high pressure conditions to in-situ grow MOF-808 crystals on the polyacrylonitrile fiber;
[0012] (5) The obtained fiber membrane loaded with MOF-808 crystals was washed with methanol for multiple times to remove unreacted impurities, and the fiber membrane was immersed in methanol and ultrasonically vibrated for a certain period of time to remove excess MOF-808 particles that were not tightly loaded on the fiber surface. The composite fiber membrane was then laid flat between double-layer polytetrafluoroethylene templates, a certain pressure was applied, and the membrane was placed in a vacuum oven for drying;
[0013] (6) Casting the MOF-808@PAN composite fiber membrane obtained in step (5) with a double-layer polyethylene oxide polymer matrix so that the polymer matrix fully infiltrates and wraps the fiber membrane, and vacuum drying to obtain a solid electrolyte (membrane) based on a beaded MOF-808 network.
[0014] Furthermore, in step (1), the mass fraction of the spinning solution is 10%-20%, the voltage is 13-18Kv, the spinning propulsion speed is 0.0006-0.001mm / s, and the thickness of the polyacrylonitrile fiber membrane obtained by electrospinning is controlled to be between 20-50μm.
[0015] Furthermore, in step (2), the MOF-808 precursor solution is synthesized in an aqueous system, and the solvent used is deionized water.
[0016] Furthermore, in step (3), the polyacrylonitrile fiber membrane is cut into a size of 3 cm*3 cm according to the size of the reactor.
[0017] Furthermore, the growth of the beaded MOF-808 crystals on the PAN fiber membrane in step (4) is an aqueous synthesis, and the solvent used is deionized water.
[0018] Furthermore, the temperature of the hydrothermal condition in step (4) is 100°C-150°C, and the reaction time is controlled to be 10-20h.
[0019] Furthermore, in step (5), the MOF-808@PAN fiber membrane is ultrasonically oscillated in a methanol solution for 10-30 minutes.
[0020] Furthermore, the application of a certain pressure in step (5) is specifically to press a metal iron block of 50N-80N / block on the polytetrafluoroethylene template.
[0021] Furthermore, in step (5), the vacuum oven drying temperature is 60°C-80°C and the drying time is 8-12h.
[0022] Furthermore, the composite MOF-808@PAN fiber membrane obtained after drying in step (5) has a thickness between 30 and 80 μm.
[0023] Further, in step (6), the polyethylene oxide polymer matrix is a mixture of polyethylene oxide (PEO) and lithium salt (LiTFSI), the molar ratio of PEO to LiTFSI is 18:1-20:1, the solute is weighed, and the solvent is acetonitrile.
[0024] Furthermore, a MOF fiber network under high temperature and high pressure was prepared for application in solid polymer electrolytes, and the thickness of the obtained solid electrolyte based on the beaded MOF-808 network was 90-120 μm.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] Different from the existing invention patents and literatures in which MOF particles are directly synthesized and mechanically mixed into a polymer matrix to prepare polymer electrolytes, the present invention loads MOF particles on a polyacrylonitrile fiber network to form a continuous MOF chain, avoiding the physical agglomeration of MOF particles and causing uneven lithium deposition in the battery, thereby obtaining stable electrochemical performance.
[0027] Unlike the existing inventions in which MOF particles are added to the spinning solution and the MOF particles are wrapped inside the fiber through electrospinning technology to prepare the polymer electrolyte, the present invention places the fiber membrane in the MOF precursor solution and loads the beaded MOF particles on the fiber surface, which not only retains the pores between the fibers for immersion in the polymer matrix, but also allows the lithium ions immersed therein to fully utilize the high specific surface area and multiple pore sizes of MOF to form a fast continuous ion transmission channel. In addition, the MOF particles on the fiber surface expose sufficient active sites to effectively capture lithium salt anions, giving full play to the regulatory effect of the beaded continuous MOF chain on lithium salt ions.
[0028] The present invention controls the thickness of the MOF@PAN fiber membrane by controlling the thickness of the electrospun fiber membrane, as well as processes such as ultrasound and hot pressing under certain conditions, so that the thickness of the cast polymer matrix electrolyte membrane is ultimately maintained between 90 and 120 μm. A MOF fiber network under high temperature and high pressure is constructed for application in solid polymer electrolytes, effectively improving the chemical stability of the polymer electrolyte material.
[0029] The present invention realizes the use of polyacrylonitrile fiber as a carrier under high temperature and high pressure conditions, and MOF-808 crystals with a regular octahedral structure are loaded on the fiber surface in the form of "beads", so that the lithium ions impregnated therein can not only be transmitted along the continuous fiber path, but also the large sieve pore size of the fully exposed MOF-808 crystals themselves ensures the high diffusivity of lithium ions, and the active metal sites on its surface effectively capture lithium salt anions, which makes the MOF-808 network an accelerator of ion conduction, optimizes the application of metal organic framework materials in polymer electrolytes, and thus improves the long-term cycle stability of solid-state lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 a is an electron microscope image of a MOF-808@PAN fiber provided in Example 1 of the present invention; Figure 1 b is an electron microscope image of a MOF-808@PAN membrane provided in Comparative Example 1 of the present invention without applying pressure during the drying process;
[0032] Figure 2 is the surface of the solid polymer electrolyte prepared in Example 1 of the present invention ( Figure 2 a) and cross section ( Figure 2b) Electron micrograph;
[0033] Figure 3 This is a comparison diagram of impedance between Example 1 of the present invention and Comparative Examples 1-3 at 30°C;
[0034] Figure 4 is the ion migration number tested in Example 1 of the present invention;
[0035] Figure 5 This is a test chart of the cycle performance of a full battery with lithium iron phosphate as the positive electrode assembled in Example 1 of the present invention at 60°C and 0.5C. DETAILED DESCRIPTION
[0036] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] The preparation method of the solid electrolyte based on the beaded MOF-808 network in this embodiment is as follows:
[0039] Step (1): Accurately weigh 2g polyacrylonitrile and 18g N,N-dimethylformamide, place in a blue-mouth bottle and stir on a magnetic stirrer at room temperature for 6h to form a yellow transparent viscous solution. Inject the spinning solution into a 20mL syringe, select a No. 21 metal needle, set the electrospinning positive voltage to 13kv, the negative voltage to 1kv, the rotating receiver speed to 150r / min, the feed speed to 0.001mm / s, and the spinning time to 8h to obtain a white 30μm thick polyacrylonitrile fiber membrane; then place in a vacuum oven and set to activate at 60℃ for 12h; cut the activated fiber membrane into 20 uniform square pieces of 3cm*3cm for later use.
[0040] Step (2): Accurately weigh 0.78 g zirconium chloride, 0.63 g terephthalic acid, 24 mL deionized water, and 12 mL trifluoroacetic acid, place in a beaker and mix evenly, and ultrasonicate for 30 min to fully dissolve to obtain a MOF-808 precursor solution.
[0041] Step (3): Pour the MOF-808 precursor solution obtained in step (2) into a 100 mL reactor lining, then take out 8 pieces of the fiber membrane cut in step (1) and completely immerse them in the MOF-808 precursor solution in the reactor lining, set the reaction temperature to 100°C, react under high temperature and high pressure conditions for 12 hours, wait for the reactor to cool to room temperature and take out to obtain a MOF-808@PAN composite fiber membrane.
[0042] Step (4): After the MOF-808@PAN composite fiber membrane obtained in step (3) was repeatedly washed with methanol for three times, it was immersed in a methanol solution again, ultrasonicated for 10 minutes, the fiber membrane was taken out, and then rinsed with methanol twice.
[0043] Step (5): Spread the MOF-808@PAN composite fiber membrane cleaned in step (4) on a polytetrafluoroethylene template, press a 50N metal iron block on the template, and place it in a vacuum oven at 80°C for 12 hours to obtain a MOF-808@PAN composite fiber membrane with a thickness of 50 μm.
[0044] Step (6): In a glove box, accurately weigh 2.76 g of polyethylene oxide and 1 g of lithium salt into a blue-mouth bottle, then pour in 60 g of acetonitrile solvent, seal with sealing glue, and place on a magnetic stirrer for vigorous stirring for 12 h to obtain a PEO / LiTFSI solution; take a polytetrafluoroethylene mold with a diameter of 8 cm and a depth of 3 cm, first pour 5 mL of PEO / LiTFSI solution to make it evenly spread, then lay 3 pieces of MOF-808@PAN composite fiber membranes prepared in step (5), and cast a layer of 5 mL of PEO / LiTFSI solution again to evenly cover the fiber membrane; place the prepared composite polymer in a vacuum oven, vacuum dry at 60°C for 24 h to evaporate the solvent, and obtain a composite beaded MOF-808 network polymer electrolyte with a thickness of 90 μm.
[0045] Example 2
[0046] The preparation method of the solid electrolyte based on the beaded MOF-808 network in this embodiment is as follows:
[0047] Step (1): Accurately weigh 2g polyacrylonitrile and 18g N,N-dimethylformamide, place in a blue-mouth bottle and stir on a magnetic stirrer at room temperature for 6h to form a yellow transparent viscous solution. Inject the spinning solution into a 20mL syringe, select a No. 21 metal needle, set the electrospinning positive voltage to 15kv, the negative voltage to 1kv, the rotating receiver speed to 150r / min, the feed speed to 0.001mm / s, and the spinning time to 7h to obtain a white 20μm thick polyacrylonitrile fiber membrane; then place in a vacuum oven and set to activate at 60℃ for 12h; cut the activated fiber membrane into 20 uniform square pieces of 3cm*3cm for later use.
[0048] Step (2): Accurately weigh 0.78 g zirconium chloride, 0.63 g terephthalic acid, 24 mL deionized water, and 12 mL trifluoroacetic acid, place in a beaker and mix evenly, and ultrasonicate for 30 min to fully dissolve to obtain a MOF-808 precursor solution.
[0049] Step (3): Pour the MOF-808 precursor solution obtained in step (2) into a 100 mL reactor lining, then take out 8 pieces of the fiber membrane cut in step (1) and completely immerse them in the MOF-808 precursor solution in the reactor lining, set the reaction temperature to 120°C, react under high temperature and high pressure conditions for 10 hours, wait for the reactor to cool to room temperature and take out to obtain a MOF-808@PAN composite fiber membrane.
[0050] Step (4): After the MOF-808@PAN composite fiber membrane obtained in step (3) was repeatedly washed with methanol for three times, it was immersed in a methanol solution again, ultrasonicated for 20 minutes, the fiber membrane was taken out, and then rinsed with methanol twice.
[0051] Step (5): Spread the MOF-808@PAN composite fiber membrane cleaned in step (4) on a polytetrafluoroethylene template, press a 60N metal iron block on the template, and place it in a vacuum oven at 60°C for 12 hours to obtain a MOF-808@PAN composite fiber membrane with a thickness of 60 μm.
[0052] Step (6): In a glove box, accurately weigh 2.76 g of polyethylene oxide and 1 g of lithium salt into a blue-mouth bottle, then pour in 60 g of acetonitrile solvent, seal with sealing glue, and place on a magnetic stirrer for vigorous stirring for 12 h to obtain a PEO / LiTFSI solution; take a polytetrafluoroethylene mold with a diameter of 8 cm and a depth of 3 cm, first pour 6 mL of PEO / LiTFSI solution to make it evenly spread, then lay 3 pieces of MOF-808@PAN composite fiber membranes prepared in step (5), and cast a layer of 6 mL of PEO / LiTFSI solution again to evenly cover the fiber membrane; place the prepared composite polymer in a vacuum oven, vacuum dry at 60°C for 24 h to evaporate the solvent, and obtain a composite beaded MOF-808 network polymer electrolyte with a thickness of 102 μm.
[0053] Example 3
[0054] The preparation method of the solid electrolyte based on the beaded MOF-808 network in this embodiment is as follows:
[0055] Step (1): Accurately weigh 2g polyacrylonitrile and 18g N,N-dimethylformamide, place in a blue-mouth bottle and stir on a magnetic stirrer at room temperature for 6h to form a yellow transparent viscous solution. Inject the spinning solution into a 20mL syringe, select a No. 21 metal needle, set the electrospinning positive voltage to 16kv, the negative voltage to 1kv, the rotating receiver speed to 150r / min, the feed speed to 0.001mm / s, and the spinning time to 8h to obtain a white 40μm thick polyacrylonitrile fiber membrane; then place in a vacuum oven and set to activate at 60℃ for 12h; cut the activated fiber membrane into 20 uniform square pieces of 3cm*3cm for later use.
[0056] Step (2): Accurately weigh 0.78 g zirconium chloride, 0.63 g terephthalic acid, 24 mL deionized water, and 12 mL trifluoroacetic acid, place in a beaker and mix evenly, and ultrasonicate for 30 min to fully dissolve to obtain a MOF-808 precursor solution.
[0057] Step (3): Pour the MOF-808 precursor solution obtained in step (2) into a 100 mL reactor lining, then take out 8 pieces of the fiber membrane cut in step (1) and completely immerse them in the MOF-808 precursor solution in the reactor lining, set the reaction temperature to 150°C, react under high temperature and high pressure conditions for 10 hours, wait for the reactor to cool to room temperature and take out to obtain a MOF-808@PAN composite fiber membrane.
[0058] Step (4): After the MOF-808@PAN composite fiber membrane obtained in step (3) was repeatedly washed with methanol for three times, it was immersed in a methanol solution again, ultrasonicated for 30 minutes, the fiber membrane was taken out, and then rinsed with methanol twice.
[0059] Step (5): Spread the MOF-808@PAN composite fiber membrane cleaned in step (4) on a polytetrafluoroethylene template, press a 70N metal iron block on the template, and place it in a vacuum oven at 80°C for 12 hours to obtain a MOF-808@PAN composite fiber membrane with a thickness of 70 μm.
[0060] Step (6): In a glove box, accurately weigh 2.76 g of polyethylene oxide and 1 g of lithium salt into a blue-mouth bottle, then pour in 60 g of acetonitrile solvent, seal with sealing glue, and place on a magnetic stirrer for vigorous stirring for 12 h to obtain a PEO / LiTFSI solution; take a polytetrafluoroethylene mold with a diameter of 8 cm and a depth of 3 cm, first pour 7 mL of PEO / LiTFSI solution to make it evenly spread, then lay 3 pieces of MOF-808@PAN composite fiber membranes prepared in step (5), and cast another layer of 7 mL of PEO / LiTFSI solution to evenly cover the fiber membrane; place the prepared composite polymer in a vacuum oven, vacuum dry at 60°C for 24 h to evaporate the solvent, and obtain a composite beaded MOF-808 network polymer electrolyte with a thickness of 110 μm.
[0061] Example 4
[0062] The preparation method of the solid electrolyte membrane based on the beaded MOF-808 network in this embodiment is as follows:
[0063] Step (1): Accurately weigh 2g polyacrylonitrile and 18g N,N-dimethylformamide, place in a blue-mouth bottle and stir on a magnetic stirrer at room temperature for 6h to form a yellow transparent viscous solution. Inject the spinning solution into a 20mL syringe, select a No. 21 metal needle, set the electrospinning positive voltage to 18kv, the negative voltage to 1kv, the rotating receiver speed to 150r / min, the feed speed to 0.001mm / s, and the spinning time to 8h to obtain a white 50μm thick polyacrylonitrile fiber membrane; then place in a vacuum oven and set to activate at 60℃ for 12h; cut the activated fiber membrane into 20 uniform square pieces of 3cm*3cm for later use.
[0064] Step (2): Accurately weigh 0.78 g zirconium chloride, 0.63 g terephthalic acid, 24 mL deionized water, and 12 mL trifluoroacetic acid, place in a beaker and mix evenly, and ultrasonicate for 30 min to fully dissolve to obtain a MOF-808 precursor solution.
[0065] Step (3): Pour the MOF-808 precursor solution obtained in step (2) into a 100 mL reactor lining, then take out 8 pieces of the fiber membrane cut in step (1) and completely immerse them in the MOF-808 precursor solution in the reactor lining, set the reaction temperature to 100°C, react under high temperature and high pressure conditions for 12 hours, wait for the reactor to cool to room temperature and take out to obtain a MOF-808@PAN composite fiber membrane.
[0066] Step (4): After the MOF-808@PAN composite fiber membrane obtained in step (3) was repeatedly washed with methanol for three times, it was immersed in a methanol solution again, ultrasonicated for 20 minutes, the fiber membrane was taken out, and then rinsed with methanol twice.
[0067] Step (5): Spread the MOF-808@PAN composite fiber membrane cleaned in step (4) on a polytetrafluoroethylene template, press a metal iron block weighing 80N on the template, and place it in a vacuum oven at 80°C for 12 hours to obtain a MOF-808@PAN composite fiber membrane with a thickness of 80 μm.
[0068] Step (6): In a glove box, accurately weigh 2.76 g of polyethylene oxide and 1 g of lithium salt into a blue-mouth bottle, then pour in 60 g of acetonitrile solvent, seal with sealing glue, and place on a magnetic stirrer for vigorous stirring for 12 h to obtain a PEO / LiTFSI solution; take a polytetrafluoroethylene mold with a diameter of 8 cm and a depth of 3 cm, first pour 8 mL of PEO / LiTFSI solution to make it evenly spread, then lay 3 pieces of MOF-808@PAN composite fiber membranes prepared in step (5), and cast another layer of 8 mL of PEO / LiTFSI solution to evenly cover the fiber membrane; place the prepared composite polymer in a vacuum oven, vacuum dry at 60°C for 24 h to evaporate the solvent, and obtain a composite beaded MOF-808 network polymer electrolyte with a thickness of 118 μm.
[0069] Comparative Example 1
[0070] This comparative example provides a solid electrolyte membrane, which does not add a MOF network, but only adds the polyacrylonitrile fiber membrane in step (1), and casts a PEO polymer matrix according to the process of step (6) to prepare a solid polymer electrolyte membrane, except that no MOF material is added. The specific steps are as follows:
[0071] Step (1): Accurately weigh 2g polyacrylonitrile and 18g N,N-dimethylformamide, place in a blue-mouth bottle and stir on a magnetic stirrer at room temperature for 6h to form a yellow transparent viscous solution. Inject the spinning solution into a 20mL syringe, select a No. 21 metal needle, set the electrospinning positive voltage to 13kv, the negative voltage to 1kv, the rotating receiver speed to 150r / min, the feed speed to 0.001mm / s, and the spinning time to 8h to obtain a white 30μm thick polyacrylonitrile fiber membrane; then place in a vacuum oven and set to activate at 60℃ for 12h; cut the activated fiber membrane into 20 uniform square pieces of 3cm*3cm for later use.
[0072] Step (2): In a glove box, accurately weigh 2.76 g of polyethylene oxide and 1 g of lithium salt into a blue-mouth bottle, then pour in 60 g of acetonitrile solvent, seal with sealing glue, and place on a magnetic stirrer for vigorous stirring for 12 h to obtain a PEO / LiTFSI solution; take a polytetrafluoroethylene mold with a diameter of 8 cm and a depth of 3 cm, first pour 5 mL of PEO / LiTFSI solution to make it evenly spread, then lay 3 pieces of fiber membranes in step (1), and cast a layer of 5 mL of PEO / LiTFSI solution again to evenly cover the fiber membrane; place the prepared composite polymer in a vacuum oven, and vacuum dry it at 60°C for 24 h to evaporate the solvent to obtain a solid electrolyte.
[0073] Comparative Example 2
[0074] This comparative example provides a solid electrolyte membrane, which is an added MOF network. The difference from Example 1 is that only the pressure of the drying process in step (5) of Example 1 is changed, and no pressure is applied during the drying process. The other steps are completely the same. The specific changed steps are as follows:
[0075] Step (5): The MOF-808@PAN fiber membrane cleaned in step (4) was spread flat on a polytetrafluoroethylene template and directly placed in a vacuum oven at 80° C. to dry for 12 h.
[0076] Comparative Example 3
[0077] This comparative example provides a solid electrolyte membrane, which is a solid electrolyte membrane with an added MOF network. What is changed is the thickness of the beaded MOF-808 network polymer electrolyte membrane. The difference from Example 1 is that only the amount of the PEO / LiTFSI solution cast in step (6) of Example 1 is changed, and the other steps are completely the same. The specific changed steps are as follows:
[0078] Step (6): In a glove box, accurately weigh 2.76 g of polyethylene oxide and 1 g of lithium salt into a blue-mouth bottle, then pour in 60 g of acetonitrile solvent, seal with sealing glue, and place on a magnetic stirrer for vigorous stirring for 12 h to obtain a PEO / LiTFSI solution; take a polytetrafluoroethylene mold with a diameter of 8 cm and a depth of 3 cm, first pour 10 mL of PEO / LiTFSI solution to make it evenly spread, then lay 3 pieces of fiber membranes in step (5), and cast a layer of 10 mL of PEO / LiTFSI solution again to evenly cover the fiber membrane; place the prepared composite polymer in a vacuum oven, vacuum dry at 60°C for 24 h to evaporate the solvent, and obtain a composite beaded MOF-808 network polymer electrolyte with a thickness of 130 μm.
[0079] Performance Testing
[0080] Electrochemical impedance spectroscopy (EIS) measurements were performed on an electrochemical workstation (Gamry) with a frequency range of 0.1 Hz to 2 MHz. The test temperature range was 30 to 70 °C, and then according to the formula The ionic conductivity σ was calculated; the lithium ion transfer number (t(Li+)) of the electrolyte was measured by the timed current method in a symmetric lithium-ion battery with a direct current (DC) polarization voltage of 10 mV, and the AC impedance was also measured. The lithium symmetric battery and the lithium full battery were charged and discharged on a LANHE, CT2001A battery tester (LAND). All electrochemical measurements were performed at 60°C.
[0081] Results Analysis
[0082] Figure 1 a shows an electron microscope image of a beaded MOF-808@PAN fiber network in Example 1. The individual MOF-808 crystals reach micrometer-level size, and the MOF-808 chains are connected in series by continuous polyacrylonitrile fibers. Figure 1 As shown in Figure b, if no pressure is applied during the drying process of the MOF-808@PAN composite membrane, the MOF-808 particles will be too aggregated and unable to form obvious chains. Therefore, the condition of applying pressure is particularly important. Figure 2 a and Figure 2 b shows the surface and cross-section of the polymer electrolyte membrane with the addition of the MOF-808 network. It can be seen that after treatment in different steps, the thickness of the high-temperature and high-pressure MOF network applied to the polymer electrolyte membrane is controlled at 90 μm, which facilitates rapid ion transport.
[0083] Figure 3From the impedances of Example 1 and Comparative Examples 1-3 at 30°C, it can be seen that the polymer electrolyte with the addition of the beaded MOF-808 network fully exerts the inherent advantages of MOF-808 and greatly reduces the electrochemical impedance, while an overly thick polymer electrolyte membrane will increase the impedance and reduce the ion transfer efficiency. Figure 4 The ion migration number of Example 1 was obtained to be 0.42. Figure 5 At 60°C and 0.5C, Example 1 cycled stably for 120 cycles with almost no capacity decay, and the initial specific capacity was 125 mAh g -1 It can be seen that the addition of the beaded MOF-808 network is beneficial to the stable long-term cycle of the battery.
[0084] The present invention immerses an ultra-thin fiber membrane prepared by electrospinning technology into a MOF-808 precursor solution, and then transfers it to a reactor to prepare a MOF-808@PAN fiber membrane under high temperature and high pressure reaction conditions. Then the composite fiber membrane is hot-pressed under a certain pressure to obtain a three-dimensional fiber network loaded with beaded MOF-808 crystals, and finally a PEO polymer matrix is layered and cast on the composite fiber membrane to obtain a solid polymer electrolyte. The present invention realizes that under high temperature and high pressure conditions, polyacrylonitrile fiber is used as a carrier, and the MOF-808 crystals with a regular octahedral structure are loaded on the fiber surface in the form of "beads", so that the lithium ions infiltrated therein can not only be transmitted along a continuous fiber path, but also the large sieve aperture of the fully exposed MOF-808 crystals themselves ensures the high diffusivity of lithium ions, and the active metal sites on its surface effectively capture lithium salt anions, which makes the MOF-808 network an accelerator of ion conduction, optimizes the application of metal organic framework materials in polymer electrolytes, and thus improves the long-term cycle stability of solid-state lithium batteries.
[0085] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and improvement made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A solid electrolyte based on a beaded MOF-808 network, characterized in that: The beaded MOF-808 network uses polyacrylonitrile (PAN) fibers as carriers, and large-particle MOF-808 single crystal structures with regular octahedral structures are loaded on the polyacrylonitrile fiber network in a beaded manner; the beaded MOF-808 fiber network is wrapped in a polymer matrix.
2. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 1, characterized in that: The following steps are involved: 1) Preparation of PAN fiber membrane by electrospinning; 2) placing the PAN fiber membrane in step 1) in a MOF-808 precursor solution and placing them together in a high-pressure reactor to in-situ grow MOF-808 crystals under hydrothermal conditions to obtain a composite MOF-808@PAN fiber membrane loaded with beaded MOF-808 crystals; 3) The composite MOF-808@PAN fiber membrane in step 2) was washed with methanol and ultrasonically vibrated, and then washed with methanol again. Then, the composite MOF-808@PAN fiber membrane was laid flat between the double-layer polytetrafluoroethylene templates, and placed in a vacuum oven for drying while applying a certain pressure; 4) Casting the composite MOF-808@PAN fiber membrane obtained after drying in step 3) with a double-layer polyethylene oxide polymer matrix, so that the polyethylene oxide polymer matrix fully infiltrates and wraps the composite MOF-808@PAN fiber membrane, and vacuum drying to obtain a solid electrolyte based on a beaded MOF-808 network.
3. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 2, characterized in that: In the step 1), the thickness of the PAN fiber membrane obtained by electrospinning is controlled between 20-50 μm.
4. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 2, characterized in that: In the step 2), the growth of the beaded MOF-808 crystals on the PAN fiber membrane is an aqueous synthesis, and the solvent used is deionized water.
5. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 2 or 4, characterized in that: The temperature of the hydrothermal condition in step 2) is 100° C.-150° C., and the reaction time is controlled to be 10-20 hours.
6. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 2, characterized in that: In the step 3), the MOF-808@PAN fiber membrane is ultrasonically oscillated in a methanol solution for 10-30 minutes.
7. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 2, characterized in that: The pressure applied in step 3) is 50N-80N, the drying temperature is 60°C-80°C, and the drying time is 8-12h.
8. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 2, characterized in that: The thickness of the composite MOF-808@PAN fiber membrane obtained after drying in step (3) is between 30 and 80 μm.
9. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 2, characterized in that: In the step 4), the polyethylene oxide polymer matrix is a mixture of polyethylene oxide (PEO) and lithium salt (LiTFSI), the molar ratio of PEO to LiTFSI is 18:1-20:1, the solute is weighed, and the solvent is acetonitrile.
10. The method for preparing a solid electrolyte based on a beaded MOF-808 network according to claim 2 or 9, characterized in that: A MOF fiber network under high temperature and high pressure was prepared for application in solid polymer electrolytes. The thickness of the obtained solid electrolyte based on the beaded MOF-808 network was 90-120 μm.